Comoclathris acuminata (Pleosporaceae, Pleosporales): A new endophytic species from Indian Himalayas - Mattoo, Aroosa Jan; Ghosh, Aniket; Nonzom, Skarma (Phytotaxa, 2023)
An interesting endophytic fungus was isolated from the stem of Ephedra gerardiana growing in Ladakh, a cold arid desert and a part of trans-Himalayan region in Northwest India. Based on comprehensive cultural, micro-morphological, and phylogenetic analyses, the isolate was identified as a new species of the genus Comoclathris, proposed herein as C. acuminata. The novelty of the taxon was strongly supported by the concatenated dataset based on nuclear ribosomal internal transcribed spacer (nrITS) and large subunit (nrLSU) regions of DNA. It is characterized by predominantly superficial, dark-brown to black, ostiolate ascomata, cylindro-clavate asci, and muriform ascospores. Comoclathris acuminata differs from other known species of Comoclathris in bearing ascospores with a prominent beak-like or pointed apex. A detailed description, illustrations and phylogenetic results of the new species are provided along with its comparison with the allied species.